Sharing Emotions Contributes to Regulating Collaborative Intentions in Group Problem-Solving - Avry, Sunny; Molinari, Gaëlle; Bétrancourt, Mireille; Chanel, Guillaume (Frontiers in Psychology, 2020)
Collaborative problem-solving has been gaining attention as more and more students and employees work together all around the world to find solutions to complex problems. This trend goes hand in hand with a growing interest in the role of affective processes in learning and problem-solving fields. However, the comprehension of real-time dynamics between emotional sharing and collaborative exchanges (what we propose to call “collaborative act”) still needs to be deepened. The challenge is especially on understanding the interplay between real-time changes in epistemic and relational dimensions. In this study, we propose to explore this question in dyadic creative problem-solving. Eleven pairs of participants used an argument graph tool to co-create a slogan against violence at school. The tool was used to write down slogans and build a joint map of the group argumentation. During the collaboration, they had access to an emotion awareness tool, allowing them to share emotional labels in real-time. An indicator of real-time use was computed to track ongoing changes in collaborative acts during collaboration. Then, using both inferential and descriptive statistics, we first investigated whether emotional sharing induces real-time adaptation of both emitter and receiver’s collaborative acts. Second, we looked at privileged relationships between emitter’s collaborative acts, emitter’s emotion sharing and receiver’s collaborative acts. The preliminary results obtained 1) confirm that emotional sharing regulates emitter’s and receiver’s collaborative acts, and 2) strongly suggest that specific emotions mark specific patterns of collaboration in different collaborative phases, implying both the epistemic and relational spaces of collaboration. These results highlight the value of studying emotional sharing for a deeper comprehension of the factors regulating collaborative problem-solving. Perspectives in educational psychology and computer science are considered, with the will to understand and promote better self and co-regulation of collaborative problem-solving through emotional sharing.